2001
DOI: 10.1530/rep.0.1210553
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of matrix metalloproteinases 2 and 9 and tissue inhibitor of metalloproteinases into follicular fluid during follicle development in equine ovaries

Abstract: Extensive tissue remodelling is required in equine ovaries for follicle growth and development and also migration of the follicle to the ovulatory fossa, where ovulation occurs. The mechanisms for these processes are largely unexplored. Matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs) are important for control of breakdown of extracellular matrix during tissue remodelling. The aims of this study were to determine the pattern and sites of secretion of the gelatinases MMP-2 and -9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…Bagavandoss et al [17] reported that the presence of MMP-2 in the neonatal ovary suggests that it functions in follicular development. Although MMP-9 levels increase when follicle diameter increases, MMP-2 levels are similar at all stages of follicular development [18]. Imai et al [19] suggested that MMP-2 activity, in particular, in follicular fluid could serve as a marker of follicular health, whereas an abundance of pro-MMP-9 could possibly denote a follicular cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Bagavandoss et al [17] reported that the presence of MMP-2 in the neonatal ovary suggests that it functions in follicular development. Although MMP-9 levels increase when follicle diameter increases, MMP-2 levels are similar at all stages of follicular development [18]. Imai et al [19] suggested that MMP-2 activity, in particular, in follicular fluid could serve as a marker of follicular health, whereas an abundance of pro-MMP-9 could possibly denote a follicular cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Portions (10 mL) of concentrate were electrophoresed under native, nondenaturing conditions on a 7.5% polyacrylamide gel containing 10% gelatin as substrate. Zymographic analysis was then carried out by previously published methods (15). Intensity of digested bands was quantified using Open lab image analysis software (Improvision, Coventry, United kingdom) after densitometric scanning (BioRad Laboratories Ltd., Hemel Hempstead, United Kingdom).…”
Section: Gelatin Zymographymentioning
confidence: 99%
“…Matrix metalloproteinase-9 was elevated in fluid of preovulatory follicles of pigs [95] and horses [96] and in formative corpora lutea or luteinized granulosa cells of rats [97], cattle [98,99], and human beings [100]. Collagenase-3 (MMP-13), which degrades collagens I-III, was increased in preovulatory rat follicles [101,102].…”
Section: Additional Considerationsmentioning
confidence: 99%